2013
DOI: 10.1016/j.aquaculture.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal control of tryptic enzyme activity in Atlantic cod larvae (Gadus morhua): Involvement of cholecystokinin during ontogeny and diurnal rhythm

Abstract: Please cite this article as: Tillner, Robert, Rønnestad, Ivar, Harboe, Torstein, Ueberschär, Bernd, Hormonal control of tryptic enzyme activity in Atlantic cod larvae (Gadus morhua): Involvement of cholecystokinin during ontogeny and diurnal rhythm, Aquaculture (2013Aquaculture ( ), doi: 10.1016Aquaculture ( /j.aquaculture.2013 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…The first direct evidence of the actions of CCK on feeding was provided by injections in goldfish (Himick and Peter, 1994), followed by cloning of goldfish CCK cDNA (Peyon et al, 1998) and the demonstration of periprandial variations in CCK mRNA expression levels (Peyon et al, 1999). Subsequently, a number of studies have characterized CCK in several fish, including other Cypriniformes (e.g., common carp Zhong et al, 2013; zebrafish Koven and Schulte, 2012; Tian et al, 2015; grass carp; blunt snout bream Ping et al, 2013; Ji et al, 2015), Characiformes (e.g., cavefish Wall and Volkoff, 2013, dourado Pereira et al, 2015; Volkoff et al, 2016, thin dogfish Oligosarcus hepsetus Vieira-Lopes et al, 2013, pirapitinga Volkoff, 2015a, red-bellied piranha Volkoff, 2014a, pacu Volkoff et al, 2017), Salmoniformes (e.g., Atlantic salmon Valen et al, 2011), Gadiformes (Atlantic cod Tillner et al, 2013), Perciformes [e.g., yellowtail (Furutani et al, 2013; Hosomi et al, 2014); Astatotilapia burtoni (Grone et al, 2012); cunner (Babichuk and Volkoff, 2013; Hayes and Volkoff, 2014); sea bass (Tillner et al, 2014); yellow croaker ( Larimichthys crocea ) (Cai et al, 2015); white sea bream, Diplodus sargus (Micale et al, 2012, 2014)], Pleuronectiformes (e.g., winter flounder (MacDonald and Volkoff, 2009a), Atlantic halibut Kamisaka et al, 2001, olive flounder Kurokawa et al, 2000) and Siluriformes (channel catfish Peterson et al, 2012). …”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…The first direct evidence of the actions of CCK on feeding was provided by injections in goldfish (Himick and Peter, 1994), followed by cloning of goldfish CCK cDNA (Peyon et al, 1998) and the demonstration of periprandial variations in CCK mRNA expression levels (Peyon et al, 1999). Subsequently, a number of studies have characterized CCK in several fish, including other Cypriniformes (e.g., common carp Zhong et al, 2013; zebrafish Koven and Schulte, 2012; Tian et al, 2015; grass carp; blunt snout bream Ping et al, 2013; Ji et al, 2015), Characiformes (e.g., cavefish Wall and Volkoff, 2013, dourado Pereira et al, 2015; Volkoff et al, 2016, thin dogfish Oligosarcus hepsetus Vieira-Lopes et al, 2013, pirapitinga Volkoff, 2015a, red-bellied piranha Volkoff, 2014a, pacu Volkoff et al, 2017), Salmoniformes (e.g., Atlantic salmon Valen et al, 2011), Gadiformes (Atlantic cod Tillner et al, 2013), Perciformes [e.g., yellowtail (Furutani et al, 2013; Hosomi et al, 2014); Astatotilapia burtoni (Grone et al, 2012); cunner (Babichuk and Volkoff, 2013; Hayes and Volkoff, 2014); sea bass (Tillner et al, 2014); yellow croaker ( Larimichthys crocea ) (Cai et al, 2015); white sea bream, Diplodus sargus (Micale et al, 2012, 2014)], Pleuronectiformes (e.g., winter flounder (MacDonald and Volkoff, 2009a), Atlantic halibut Kamisaka et al, 2001, olive flounder Kurokawa et al, 2000) and Siluriformes (channel catfish Peterson et al, 2012). …”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…It has been suggested that ingested protein may have a regulatory function by competing as a substrate for trypsin, thereby preventing the inactivation of the cck‐releasing factor (Liddle, 2000; Rønnestad, Kamisaka, Conceição, Morais, & Tonheim, 2007). In this sense, studies in Gadus morhua larvae have suggested that a negative feedback mechanism is present between cck and trypsin activity (Tillner, Rønnestad, Harboe, & Ueberschär, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessment of digestive enzymes, paralleled to histo‐morphological development of digestive system, could represent a first step towards the study of hormonal mechanisms (i.e., by cholecystokinin, Micale et al, ; Tillner et al, ) involved in digestive processes during ontogeny in zebrafish. Moreover, during the larval period all organs and systems are functional, making larvae physiologically equivalent to adults.…”
Section: Discussionmentioning
confidence: 99%